The Effect of using E-Booklet Counseling on Interest in Rotavirus Immunization in Children 2 Months at Samboja Puskesmas Year 2023 - Yeni Marliani; Nina Mardiana; Damai Noviasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Diarrhea is a problem that generally affects toddlers and is the main cause of dehydration. To overcome the increasing incidence of diarrhea in Indonesia, rotavirus immunization is a basic immunization. The type of research is quasi-experimental with a non-aquavalent control group pre and post test design. The population, namely all mothers who gave birth in early January 2023 at the Samboja Community Health Center, is 25 people. The sampling technique is total sampling, with a sample of 20 people divided into an intervention group of 10 people and a control group of 10 people. Data analysis used the independent t test. Characteristics of the respondents in the intervention and control groups were that most of them were aged between 20-35 years, had completed high school education and were housewives. Interest in rotavirus immunization in children aged 2 months before providing counseling using e-booklet media in the intervention group was highest among respondents with low interest.